(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The aim of this paper is to elaborate a brief analysis about the conditions and access of disabled people to health services. The methodology consist in a descriptive process of health services for disabled people in the country. The information is provided by the Nicaraguan Disabled Survey (ENDIS, for its acronym in Spanish), realized in 2003 by the National Institute of Statistics and Censuses (INEC). From the results generated by the survey, the first database of disabled people is created in the country. The survey reflects that the disability in the country is 10.3 % of the six-year-old major population, 10.5 % in the urban area and 10 % in the rural zones, it also shows that the disability affects more to female, 11,3 % than male (9,1 %).